Teaching medical students on the ethical dimensions of human rights: meeting the challenge in South Africa. Issue 4 (August 1998) - London, L; McCarthy, G
Abstract : SETTING: Previous health policies in South Africa neglected the teaching of ethics and human rights to health professionals. In April 1995, a pilot course was run at the University of Cape Town in which the ethical dimensions of human rights issues in South Africa were explored. OBJECTIVES: To compare knowledge and attitudes of participating students with a group of control students. DESIGN: Retrospective cohort study. SUBJECTS: Seventeen fourth-year medical students who participated in the course and 13 control students from the same class, matched for gender. INTERVENTIONS: Students participated in a one-week module on ethics and human rights. Five months after the course had been run, students completed a semi-structured questionnaire exploring their knowledge and attitudes with regards to ethics and human rights issues. MAIN OUTCOME MEASURES: Knowledge scores, attitude scores and various individual indicators of attitude. RESULTS: Clear benefits for overall knowledge score, for four out of five individual knowledge questions and for one of the attitude questions, were demonstrated. Participating students also appeared to be more convinced of the need for teaching on the ethical dimensions of human rights at postgraduate level and that such teaching should also be integrated in the curriculum. The low response rate amongst controls may have selected students who were more socially conscious, thereby leading to an underestimate of the true impact of the course. CONCLUSION: The evaluation indicates clear benefits of the course for undergraduate students, and supports arguments for the inclusion of such courses in the training of health professionals. This is particularly important given the challenges posed by the Truth and Reconciliation Commission to the health professions to address past complicity in human rights abuses through reorientation of medical training in South Africa.